2016
DOI: 10.3168/jds.2015-10661
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of postruminal microbial nitrogen flows in dairy cattle. I. Derivation of equations

Abstract: The objective was to summarize the literature and derive equations that relate the chemical composition of diet and rumen characteristics to the intestinal supply of microbial nitrogen (MicN), efficiency of microbial protein synthesis (EMPS), and flow of nonammonia nonmicrobial N (NANMN). In this study, 619 treatment means from 183 trials were assembled for dairy cattle sampled from the duodenum or omasum. Backward elimination multiple regression was used to derive equations to estimate flow of nitrogenous com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 47 publications
1
54
0
1
Order By: Relevance
“…Studies that have directly compared N flows using omasal and duodenal sampling indicate that they are comparable (Ahvenjärvi et al, 2000;Rotta et al, 2014), although in the study of Ahvenjärvi et al (2000) where microbial NAN was also determined, it tended to be higher in the omasal canal than in the duodenum. Roman-Garcia et al (2016) in a meta-analysis reported a greater microbial N and smaller NANMN flows for omasal sampling than for duodenal sampling. An indirect validation based on the relationships between omasal NAN flow and milk protein yield derived using meta-analysis also showed that omasal measurements were accurate .…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have directly compared N flows using omasal and duodenal sampling indicate that they are comparable (Ahvenjärvi et al, 2000;Rotta et al, 2014), although in the study of Ahvenjärvi et al (2000) where microbial NAN was also determined, it tended to be higher in the omasal canal than in the duodenum. Roman-Garcia et al (2016) in a meta-analysis reported a greater microbial N and smaller NANMN flows for omasal sampling than for duodenal sampling. An indirect validation based on the relationships between omasal NAN flow and milk protein yield derived using meta-analysis also showed that omasal measurements were accurate .…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 99%
“…This technique was modified by Ahvenjärvi et al (2000) and is now used widely . Most omasal sampling protocols use a triple-marker system (France and Siddons, 1986) to mathematically correct for unrepresentative digesta sampling (Ahvenjärvi et al, 2003;Broderick et al, 2010;Roman-Garcia et al, 2016), with 15 N, and to a lesser extent purine bases, employed as microbial markers . Compared with sampling from the duodenum, the omasal canal provides some advantages as a sampling site: it is less invasive, a rumen cannula suffices, secretion of endogenous N into the reticulorumen is lower than that into the duodenum, and sampling takes place before acid-pepsin hydrolysis in the abomasum (Huhtanen et al, 1997;Ahvenjärvi, 2006).…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 99%
“…Data were collected and prepared for analysis as described in Roman-Garcia et al (2016). Briefly, a literature search was conducted to identify studies that measured duodenal or omasal N flows.…”
Section: Data Collection and Preparationmentioning
confidence: 99%
“…To minimize bias from incorrectly specifying ingredients, the study-level nutrient residuals were calculated and used to adjust book values to ensure no mean bias within a study, as described in Hanigan et al (2013). Means and standard errors were collected for all response variables of interest, and when standard errors were not directly reported, calculated using error propagation (Roman-Garcia et al, 2016).…”
Section: Data Collection and Preparationmentioning
confidence: 99%
See 1 more Smart Citation